Heterojunction solar cells on flexible silicon wafers. Issue 15 (2016) - Augusto, André; Balaji, Pradeep; Jain, Harsh; Herasimenka, Stanislau Y.; Bowden, Stuart G.
ABSTRACT: Current large-scale production of flexible solar devices delivers cells with low efficiency. In this paper we present an alternative path to organic or inorganic thin films. Our cells combine the remarkable surface passivation properties of the silicon heterojunction solar cells design, and the quality of n-type Cz wafers. The cells were manufactured on 50-70 µm-thick wafers. The cells have and efficiency of 17.8-19.2%, open-circuit voltages of 735-742 mV, short-circuit currents of 34.5-35.5 mA/cm 2, and fill-factors of 72-75%. The cells are not as flexible as bare wafers. Thin cells are particular sensitive to the additional stress introduced by the busbars and the soldered ribbons. For radiuses of curvature over 8cm the cells efficiency remains the same, for radius equal to 6cm the cell efficiency drops less than 2%, and for radius equal to 4cm the drop is less than 3%. The broken fingers due to smaller bend radius lead to higher series resistance and subsequently lower field-factors.